A dimensionless analysis of a 2DOF piezoelectric vibration energy harvester. (June 2015) - Xiao, Han; Wang, Xu; John, Sabu
Abstract: In this study, a dimensionless analysis method is proposed to predict the output voltage and harvested power for a 2DOF vibration energy harvesting system. This method allows us to compare the harvesting power and efficiency of the 2DOF vibration energy harvesting system and to evaluate the harvesting system performance regardless the sizes or scales. The analysis method is a hybrid of time domain simulation and frequency response analysis approaches, which would be a useful tool for parametric study, design and optimisation of a 2DOF piezoelectric vibration energy harvester. In a case study, a quarter car suspension model with a piezoelectric material insert is chosen to be studied. The 2DOF vibration energy harvesting system could potentially be applied in a vehicle to convert waste or harmful ambient vibration energy into electrical energy for charging the battery. Especially for its application in a hybrid vehicle or an electrical vehicle, the 2DOF vibration energy harvesting system could improve charge mileage, comfort and reliability. Graphical abstract: Dimensionless resonant harvested power versus the stiffness and damping ratio. Highlights: To identify the effects of the mass and stiffness ratio on the dimensionless power or efficiency. To find the optimal stiffness ratio ( k 2 / k 1 ) for the maximum harvesting performance. To find the optimal damping ratio ( c 1 / c 2 ) compromising the performance and the relative displacement. To develop a dimensionless analysis of a 2DOF piezoelectric harvester for its performance. To investigate the effects of 2DOF harvester parameters on the harvesting frequency bandwidth.